FAKTOR-FAKTOR YANG MENENTUKAN KEPUTUSAN NASABAH MEMILIH BANK SYARIAH. STUDY KASUS PADA PELAKU BISNIS MUSLIM DI PASAR BARU DAN PASAR MANDONGA KENDARI - Aswawi, Nurafiah (Journal Economics Technology And Entrepreneur, 2024)
The objectives of this study are: (1) To explain the role of decision-making factors in encouraging Muslim business people to choose Islamic bank as places for financial transactions; (2) To explain the views of Muslim business people about the factors that encourage them to make decisions to choose Islamic bank as places consists of; for financial transactions. This research is a qualitative research using 30 informants and using qualitative data analysis according to Bugin which data reduction, data presentation, and data verification. The results of this study have shown that; (1) Attitudes of other people, situations, services, promotions and strategic locations/places are the most important factors that have influenced the decision of Muslim business people in Pasar Baru and Pasar Mandonga Kendari to choose a Sharia Bank as a place for financial transactions; (2) The views of Muslim business people in Pasar Baru and Pasar Mandonga Kendari regarding the factors that encourage them to make a decision to choose an Islamic bank as a place for financial transactions are positive views based on physical evidence, reliability, responsiveness, assurance and empathy.